Minimum Wage and Women at Work - Ntale, Anita (Akina Mama wa Afrika (AMwA), 2019)
A minimum wage is ideally the wage below which no worker in an economy should be paid. The ILO defines MW as; The minimum amount of remuneration that an employer is required to pay wage earners for the work performed during a given period, which cannot be reduced by collective agreement or an individual contract. It serves several purposes including the reduction of income poverty, income redistribution and the protection of vulnerable workers from exploitation. The protection of vulnerable workers is one of the key principles of MW legislation (DPRU 2016). In both developed and developing economies, vulnerable workers are typically marginalized groups like minorities, women, the youth and PLWDs2. When wages are determined entirely by the free market forces, these groups often do not have the bargaining power to demand higher wages especially in low-skilled sectors. This situation is even more pronounced in developing countries like Uganda because of the labour market structure. With limited wage employment, high informality, low trade union membership and significant dependence on a largely subsistence agricultural sector; elevated unemployment and underemployment levels mean that there is an over-supply of labour with more and more people willing to do the same work for less. In addition, poor pay in the formal sector contributes to the growth and expansion of the informal sector.